Rbx1 Flexible Linker Facilitates Cullin-RING Ligase Function Before Neddylation and After Deneddylation - Liu, Jin (The Biophysical Society, 2010)
In ubiquitination, cullin-RING E3 ubiquitin ligases (CRLs) assist in ubiquitin transfer from ubiquitin-conjugating enzyme E2 to the substrate. Neddylation, which involves NEDD8 transfer from E2 to E3-cullin, stimulates ubiquitination by inducing conformational change in CRLs. However, deneddylation, which removes NEDD8 from cullin, does not suppress ubiquitination in vivo, raising the question of how neddylation/deneddylation exerts its effects. Using molecular-dynamics simulations, we demonstrate that before neddylation occurs, the linker flexibility of Rbx1, a CRL component, leads to conformational changes in CRLs that allow neddylation and initiation of ubiquitination. These large NEDD8-induced conformational changes are retained after deneddylation, allowing both initiation of the ubiquitination process and ubiquitin chain elongation after deneddylation. Furthermore, mutation of lysine, the cullin residue to which NEDD8 covalently attaches, dramatically reduces CRL conformational changes, suggesting that the acceptor lysine allosterically regulates CRLs. Thus, our results imply that neddylation stimulates ubiquitination by CRL conformational control via lysine modification.